Renalase contributes to the renal protection of delayed ischaemic preconditioning via the regulation of hypoxia-inducible factor-1α - Wang, Feng (J Cell Mol Med, 2015)
Ischaemic preconditioning (IPC) attenuates acute kidney injury (AKI) from renal ischaemia reperfusion. Renalase, an amine oxidase secreted by the proximal tubule, not only degrades circulating catecholamines but also protects against renal ischaemia reperfusion injury. Here, it has been suggested that the renoprotective effect of renal IPC is partly mediated by renalase. In a model of brief intermittent renal IPC, the increased cortex renalase expression was found to last for 48 hrs. IPC significantly reduced renal tubular inflammation, necrosis and oxidative stress following renal ischaemia reperfusion injury. Such effects were attenuated by blocking renalase with an anti-renalase monoclonal antibody. We further demonstrated that renalase expression was up-regulated by hypoxia in vitro via an hypoxia-inducible factor (HIF)-1α mechanism. The IPC-induced up-regulation of renalase in vivo was also reduced by pre-treatment with an HIF-1α inhibitor, 3-(5′-Hydroxymethyl-2′-furyl)-1-benzyl indazole. In summary, the renoprotective effect of IPC is partly dependent on the renalase expression, which may be triggered by hypoxia via an HIF-1α mechanism. Endogenous renalase shows potential as a therapeutic agent for the prevention and treatment of AKI.